Insights into the academic-life balance of student-teachers as single mothers - Pecson, Ryan (Kirana Publisher (KNPub), 2024)
Preparing student-teachers to become globally competitive, productive, and resilient K-12 educators in the future was an arduous task. Adding pressure to their academic life was the reality that some simultaneously performed various roles and responsibilities. With that insight, the study presents insights into the academic-life balance of student-teachers as single mothers. The study utilizes the phenomenological design of qualitative research, specifically the DPA (Descriptive Phenomenological Analysis) to six female student-teachers who are selected using the stratified sampling technique from the College of Education (COEd) of the BPSU-Balanga Campus, Bataan, Philippines. The qualitative data are gathered using the semi-structured interview guide, and the data are treated using the DPA model proposed by Edmund Husserl. The study reveals significant challenges for single mother student-teachers in balancing academic and personal lives, including time management conflicts and impacts on academic performance. Support systems, such as family assistance, peer support, flexible scheduling, and counseling services, along with effective time management and self-care, are also identified as crucial for their success.